Enhanced photocatalytic degradation of 2-thiobenzimidazole by the tris(8-quinolinolato)cobalt(iii) complex through peroxide adduct formation: theoretical and experimental investigations. (4th March 2020) - Aguilar, Carlos Alberto Huerta; Narayanan, Jayanthi; López, José Abraham Balderas; Flores-Alamo, Marcos; Contreras, Enrique Fernando Velázquez; Gastélum, Karla Alejandra López; Alonzo, Fernando Rocha; Cabrera, Cristian Brayan Palacios; Cuevas, Alan Javier Santiago
Abstract : HOMO–LUMO influenced photocatalytic degradation of 2-thiobenzimidazole through a thermodynamically favored route has been achieved by the cobalt(iii ) Schiff base complex. Abstract : Photo-initiated oxidative degradation of 2-thiobenzimidazole (2-TBI) was studied using different semiconducting metal complexes derived from 8-hydroxyquinoline with the general formula, [MQ3 C2 H5 OH] [Q = 8-quinolinolato anion; M = Cr 3+, (CrQ3 ); Co 3+, (CoQ3 ); Fe 3+, (FeQ3 )]. The degradation kinetics was monitored via UV-vis spectroscopy perceiving the changes in absorbance to subtract. The effect of pH and visible light irradiation on degradation was studied observing a significant increment in the oxidation rate with the presence of visible light whenever CoQ3 is used as a catalyst. By using density functional theory (DFT), it was found that the transition state energy of the adduct formed between CoQ3 and H2 O2 is very low compared with other studied catalysts, which activates the formation of ˙OH radicals from H2 O2 increasing the 2-TBI degradation rate. In addition, a thermodynamically feasible degradation mechanism was proposed by calculating energy barriers involved in the 2-TBI oxidation pathway.